The HuMet Repository: Watching human metabolism at work - Weinisch, Patrick; Raffler, Johannes; Römisch-Margl, Werner; Arnold, Matthias; Mohney, Robert P.; Rist, Manuela J.; Prehn, Cornelia; Skurk, Thomas; Hauner, Hans; Daniel, Hannelore; Suhre, Karsten; Kastenmüller, Gabi (Cell reports (Cambridge), 2024)
Metabolism oscillates between catabolic and anabolic states depending on food intake, exercise, or stresses that change a multitude of metabolic pathways simultaneously. We present the HuMet Repository for exploring dynamic metabolic responses to oral glucose/lipid loads, mixed meals, 36-h fasting, exercise, and cold stress in healthy subjects. Metabolomics data from blood, urine, and breath of 15 young, healthy men at up to 56 time points are integrated and embedded within an interactive web application, enabling researchers with and without computational expertise to search, visualize, analyze, and contextualize the dynamic metabolite profiles of 2,656 metabolites acquired on multiple platforms. With examples, we demonstrate the utility of the resource for research into the dynamics of human metabolism, highlighting differences and similarities in systemic metabolic responses across challenges and the complementarity of metabolomics platforms. The repository, providing a reference for healthy metabolite changes to six standardized physiological challenges, is freely accessible through a web portal. [Display omitted] •Time-resolved metabolomic responses to six physiological challenges in healthy individuals•Subject-level response profiles for >2,600 metabolites measured in blood, urine, or breath•Three showcases of data usage for exploring human metabolism under challenge conditions•Interactive querying and visualization of response profiles and statistics at humet.org Weinisch et al. introduce the HuMet Repository (https://humet.org), a web-based resource for exploring dynamic metabolic responses of healthy subjects to six physiological stimuli, including prolonged fasting, oral glucose/lipid loads, and exercise. The repository enables searching, analyzing, and visualizing time-resolved metabolomics data comprising 2,656 metabolites in human blood, urine, or breath.